1994
DOI: 10.1002/ajpa.1330370611
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of breastfeeding structure and its relation to human reproductive ecology

Abstract: Although a controversial issue in the not distant past, it is now well established that breastfeeding is the primary factor mediating post-partum subfecundity. This complex interaction between behavior and physiology is a central research focus in several fields sharing a common concern with the mechanisms that regulate human reproduction. Despite the demonstrated linkage between lactation and return of the first postpartum menses, many questions regarding the relationship between variation in breastfeeding be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 165 publications
(226 reference statements)
2
70
0
1
Order By: Relevance
“…Suckling activity was not clustered into well-defined sessions (a series of closely spaced episodes), as had been observed by Vitzthum among Quechua women (1989), but occurred instead as a series of isolated episodes, usually lasting no more than 2 or 3 min but separated by intervals longer than l min (for a nice illustration of this pattern, see Fig. 1 in Vitzthum, 1994a). The frequency of suckling increased dramatically as children approached the second half of their second year.…”
Section: Breastfeeding Patterns Among Nomadic Turkanamentioning
confidence: 59%
See 1 more Smart Citation
“…Suckling activity was not clustered into well-defined sessions (a series of closely spaced episodes), as had been observed by Vitzthum among Quechua women (1989), but occurred instead as a series of isolated episodes, usually lasting no more than 2 or 3 min but separated by intervals longer than l min (for a nice illustration of this pattern, see Fig. 1 in Vitzthum, 1994a). The frequency of suckling increased dramatically as children approached the second half of their second year.…”
Section: Breastfeeding Patterns Among Nomadic Turkanamentioning
confidence: 59%
“…Although effects on fertility of the duration of lactation have been known for some time (see Bongaarts, 1981), only recently have scientists begun to understand the impact of daily breastfeeding structure (McNeilly et al, 1988). It is now clear that this structure varies markedly among so-called natural fertility populations (Campbell and Wood, 1988), with important consequences for population differences in the timing of the resumption of menses postpartum and of the length of interbirth intervals (Gray, 1994a;Vitzthum, 1994a).…”
Section: The Ecology and Structure Of Breastfeedingmentioning
confidence: 99%
“…The now well-established area of reproductive ecology (building on biomedical research in endocrinology) has repeatedly demonstrated how such a framework can lead to insights at conceptual and physiological levels (Campbell and Wood, 1994;Ellison, 2001;Konner and Worthman, 1980;Vitzthum, 1994;Wood, 1994). The time has come for similar efforts in field-based, populationlevel research in immunology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are great individual variations in BWPs in modern traditional and industrialized human populations (Vitzthum, 1994). Individual variations in BWP cannot be discussed in most cross-sectional reconstructions, but can be in longitudinal reconstructions using isotopic signals in hair (Fuller et al, 2006a), serial sections of tooth dentin (Eerkens et al, 2011;Beaumont et al, 2013b;Eerkens and Bartelink, 2013;Henderson et al, 2014), and elemental signals in thin-sectioned tooth enamel (Humphrey et al, 2008a;Austin et al, 2013).…”
Section: Heterogeneous Bwps In One Study Groupmentioning
confidence: 99%